Efficiency and productivity of Norwegian colleges - Finn R. Førsund; Kjell Ove Kalhagen (University of Oslo, Department of Economics, 1999)
Regional colleges in Norway were reorganised in 1994 with the purpose of promoting efficiency and productivity. This is the first effort of checking what actually has happened afterwards with efficiency and productivity. DEA and Malmquist index approaches are used. Data for three years, 1994, 1995 and 1996 at a department level for about 100 units where collected by questionnaire and direct contacts. The three outputs where final exams distributed on two types; short- and long studies, and research publications. Inputs where number of academic and non-academic staff in full time equivalents, current expenses other than salaries, and building size in square metres. Typical cross section efficiency results show a large share of efficient departments, with a disproportionate number of efficient departments giving theoretical general education, and a large variation within the group of inefficient units. The difference between professional and arts and science departments may be explained by the nature of the teaching production function, but calculations for a sub-sample of professional departments (e.g. nurses, engineers, teachers) show almost the same variation within this group. The productivity change each year was mainly positive, with most departments experiencing a positive productivity effect from frontier shift, but a greater variation from positive to negative as regards the contribution from catching up. – Colleges ; efficiency ; DEA ; Malmquist productivity index
Keywords: C61; D24; I21; 330; Hochschule; Wirtschaftliche Effizienz; Produktivität; Index; Data-Envelopment-Analyse; Schätzung; Norwegen